Social Potential in the Conditions of Digitalization of Economy and Society: Evaluation and Opportunities for Development - KNIAZ SVIATOSLAV; STARUKH АNNA; SHEVCHUK ІRYNA; SKUPEIKO VASYL; HALAZ LINA; KRAMAR RUSLANA; MOSKVYAK YAROSLAVA; OGIRKO IGOR; SMIRNOVA KATERYNA; RUSYN-HRYNYK ROMAN; KOZAKEVYCH OLHA (Communications of International Proceedings, 2020)
The article is a study of social potential in the context of digitalization of the economy and society and a consideration of its opportunities for development. The study establish that the economy digitalization is one of the most widely discussed aspects of the global socio-economic process, which has numerous, multifaceted and diverse manifestations. The fact, that the growth of digital technologies entails an exponential increase of quantitative and qualitative integration changes in the society communication system is noted. It is stated that American scientist N. Negroponte proposed the term “digital economy” in 1995. The article clarifies that researchers identify five areas of digital technologies impact on economic activity and indicate their areas of implementation: the Internet of Things, Big Data, innovative 3D printers, the economy of sharing. It is stressed that the global trends of digitalization of national economic systems are the development of technologies for microelectromechanical systems (MEMS), cognitive robotics, computer-aided design (CAD), mechatronics, high-precision instruments, supersensitive sensors, signal preprocessing, cloud data, Internet. The article considers that the areas of digitalization of the economy impact on social potential are as follows: the labor market, online educational services, cybercrime and business. Digital technologies and products currently considered innovative trends in the modern socio-economic environment as the most promising for the development of social society potential are presented. The process of digitalization of goods and services production has not only technological advantages, such as a new industrialization on a digital basis, increasing the competitiveness of economic entities, etc. Despite the importance of digitalization of the national economy, public authorities should not forget that the main vector of its development is the socialization of the economy, its fulfillment, first, the social functions to ensure the welfare of households and the whole society through effective use of digital information technologies. That is why the development of various legal acts, that will implement digital technologies in public life and at the same time protect the rights of citizens, deserves special attention.
Keywords: Digitalization; Digital Economy; Society; Social Potential.